Associations Between Loneliness, Reading Ability and Episodic Memory in Non-Hispanic Black and White Older Adults. (8th February 2021) - Sol, Ketlyne; Sharifian, Neika; Manly, Jennifer J; Brickman, Adam M; Zahodne, Laura B
Abstract: Objective: Reading ability reflects a variety of beneficial life course exposures and may better index these exposures above and beyond education in racially diverse samples. Growing evidence suggests a negative impact of perceived loneliness on late-life cognitive health when parsing out the effect of other aspects of social relations. Few studies have examined how loneliness interacts with the reading ability or whether it operates differently in Black older adults who have higher dementia risk than Whites. Methods: Participants in this cross-sectional study were drawn from the Washington Heights-Inwood Columbia Aging Project ( n = 425 older adults, M age = 74.23; 58% Black). Linear regressions estimated the main effects and interactions involving reading ability, loneliness, and race (non-Hispanic Black vs. non-Hispanic White) on episodic memory, controlling for age, sex/gender, and years of education. Subsequent models additionally controlled for income, employment status, depressive symptoms, disease burden, marital status, social network size, and number of social groups. Results: Higher reading ability was associated with better memory, but loneliness was not associated with memory. The positive association between reading ability and memory was weaker among individuals with greater loneliness, and this interaction did not differ by race. Conclusions: Loneliness may suppress the protective effect of higher reading ability on cognitive health among both Black and White older adults. Future longitudinal work is needed to clarify causal relationships among loneliness, reading ability, and memory decline.